Rosuvastatin safety and efficacy in coronary heart disease patients - I. V. Sergienko; M. V. Ezhov; V. P. Masenko (Кардиоваскулярная терапия и профилактика, 2006)
Aim. To study rosuvastatin safety and effects on lipid profile (LP) in coronary heart disease (CHD) patients. Material and methods. The study included 30 males (mean age 57±9 years) with diagnosed CHD, Functional Class II-III stable effort angina, receiving adequate basic therapy. In all participants, initial total cholesterol (TCH) level was >5,2 mmol/l. At baseline and after three weeks of rosuvastatin therapy (10 mg/d), general and biochemical blood assays were performed, to measure LP, AST, ALT, creatine kinase (CK), glucose, total bilirubin (BR) and creatinine levels. Results. Three-month rosuvastatin therapy improved blood LP: TCH, triglyceride (TG) and low-density lipoprotein CH (LDL-CH) levels significantly reduced, and high-density lipoprotein CH (HDL-CH) level increased. In general, levels of TCH decreased by 31%, TG – by 39%, LDL-CH – by 44%, and HDL-CH level increased by 6%. Target TCH level was achieved in 17 participants (57%), and target LDL-CH level – in 23 patients (77%). Throughout the study, no adverse reactions (hepatic enzymes, CK, BR, or glucose level increase) were observed. Conclusion. Rosuvastatin did not increase rhabdomyolysis or myopathy risk. Rosuvastatin therapy helped to achieve significant decrease in TCH and LDL-CH levels.